A unique case report on campylobacter rectus infection leading to acute motor axonal neuropathy in a pediatric patient - Uchechukwu Ibewuike, MBBS; John Kim, MD; Swati Mody, MBBS; Gregory Obala, MD; Ebere Ibezim, MBBS (Radiology Case Reports)
A unique case report on campylobacter rectus infection leading to acute motor axonal neuropathy in a pediatric patient. Campylobacter rectus is an anaerobic bacterium found in the oral cavity. While it has been linked to periodontal disease, its association with acute motor axonal neuropathy (AMAN), a variant of Guillain-Barre Syndrome, remains unverified. The majority of Guillain-Barre Syndrome (GBS) cases related to Campylobacter are attributed to the species Campylobacter jejuni. A 14-year-old male was admitted to the hospital with sepsis. About 1 week before his admission, the patient sustained an injury to his left eye from a cell phone, resulting in considerable edema. A punch biopsy of the left periorbital soft tissue yielded a culture positive for Campylobacter rectus. Following this, the patient developed weakness in all 4 limbs, with more pronounced weakness in the legs than in the arms, and he lost motor function in both lower legs, although sensory function remained intact. Analysis of cerebrospinal fluid (CSF) revealed albuminocytologic dissociation. An MRI of the spine showed anterior nerve root predominant enhancement.Electromyography was consistent with acute motor axonal neuropathy. Acute motor axonal neuropathy (AMAN), a subtype of Guillain-Barré Syndrome, arises from an atypical immune response, frequently initiated by infections caused by Campylobacter jejuni, although other infectious agents have also been identified. To the best of our knowledge, this is the first recorded instance associating Campylobacter rectus infection with AMAN.